Redox regulation of PI 3-kinase signalling via inactivation of PTEN - Leslie, Nick R. (Oxford University Press, 2003)
The tumour suppressor PTEN is a PtdIns(3,4,5)P(3) phosphatase that regulates many cellular processes through direct antagonism of PI 3-kinase signalling. Here we show that oxidative stress activates PI 3-kinase-dependent signalling via the inactivation of PTEN. We use two assay systems to show that cellular PTEN phosphatase activity is inhibited by oxidative stress induced by 1 mM hydrogen peroxide. PTEN inactivation by oxidative stress also causes an increase in cellular PtdIns(3,4,5)P(3) levels and activation of the downstream PtdIns(3,4,5)P(3) target, PKB/Akt, that does not occur in cells lacking PTEN. We then show that endogenous oxidant production in RAW264.7 macrophages inactivates a fraction of the cellular PTEN, and that this is associated with an oxidant-dependent activation of downstream signalling. These results show that oxidants, including those produced by cells, can activate downstream signalling via the inactivation of PTEN. This demonstrates a novel mechanism of regulation of the activity of this important tumour suppressor and the signalling pathways it regulates. These results may have significant implications for the many cellular processes in which PtdIns(3,4,5)P(3) and oxidants are produced concurrently.